Green Supply Chain Management Strategy in Retail Companies - Asnawi, Ikram (Maroon Journal De Management, 2024)
In the current research, the integration of the Green Supply Chain Management (GSCM) practice in the retail companies is examined, and its impact on sustainability and corporate performance are analysed. The mode of qualitative design and case-study approach was used, and data were produced by means of detailed interviewing of supply-chain managers and sustainability officers. The findings reveal that implementation of GSCM products, especially green procurement programmes and waste-reduction schemes, does not only help in shrinking the environmental footprint but also enhances the corporate reputation. However, the adoption is limited due to the high set-up fees and poor availability of certified green suppliers hence inhibiting widespread adoption. Summing up, the benefits of engaging in GSCM are significant in the long run; nevertheless, elimination of these barriers is crucial to retail businesses that seek to establish viable and lucrative operations.